The Implementation of Langkat Regent Regulation Number 19 of 2019 Concerning Procedures for Procurement of Goods and Services in Village (Study in the Village of Stabat Baru) - Mahendra Mahendra; Isnaini Isnaini; Rudi Salam Sinaga (Budapest International Research and Critics University, 2021)
The implementation of policies in the Presidential Decree PBJ has not been able to fully address the lack of community infrastructure, especially needs that are relatively simple at the village level, such as drinking water facilities, educational facilities, garbage collection, internet facilities and so on . The formulation of the research problem is how to implement and the obstacles in implementing Langkat Regent Regulation Number 19 of 2019 concerning Procedures for Procurement of Goods and Services in Village in Stabat Baru Village. The results show that the implementation in terms of communication and organizational structure has been going well, but in terms of resources and disposition it has not gone well, with the constraint factors faced in the form of difficulty coordinating with the community, lack of employee cooperation, lack of employee responsibility for work because it is more concerned with personal affairs. It is recommended that the Village Stabat Baru needs to conduct more intensive socialization regarding the importance of community involvement in PBJ. Leaders need to emphasize to employees that cooperation will be increasing important in dealing with many jobs. Leaders need to be firm in disciplining subordinates who use the working day to take care of their personal interests.